The impact of legal and organizational regulations on the nutritional behavior of patients-consumers of spa treatment services in Poland - Joanna Wozniak-Holecka; Tomasz Holecki; Kajetan Suchecki; Sylwia Jaruga-Sękowska (Frontiers Media S.A., 2022)
Health resort treatment facilities, regardless of the ownership status (public, private), most often carry out their activities based on contracts with the Polish public payer of the health care system, therefore the operation of sanatoriums is a fully-fledged element of the health care system, such as inpatient treatment, outpatient treatment and basic health care. The system designed in this way is designed to improve the organization of benefits, including by incorporating new useful organizational and legal tools. Thus, health education, along with its nutritional aspect, which is its inseparable part, is a perfect example of how to positively influence the behavior of consumers of spa treatment services. The structure of the study included the desk research method related to the consolidation and processing of information on applicable legal regulations and an individual in-depth, structured interview, using an original interview scenario. Based on the deliberate selection of the sample, 14 interviews were conducted. The interlocutors were representatives of the management of spa treatment facilities, academics and representatives of non-governmental organizations. The interview included functional and organizational, financial, competence and substantive aspects related to the implementation of nutritional education in spa treatment facilities in Poland. The use of a structured interview with experts made it possible to present the area of health education, including nutrition, in a broad light of the knowledge and experience of health care practitioners and theorists. Opinions were obtained on the optimal methods of assessing the effectiveness of education in the conditions of spa treatment and a set of system and organizational recommendations. Reporting of the results was presented using the COREQ checklist. It is justified to consider broadly understood health education in spa treatment facilities as a kind of wholesome health service, which may constitute effective systemic support for health policy and, consequently, increase the importance of prophylaxis and improve the health condition of the population. Such a legislative change will force organizational changes that may ultimately lead to a change in eating habits. Moreover, it is highly useful to use the potential of paramedical professionals, including dieticians, health educators and health promotion specialists.